If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 28x = 0 Solving ax + 28x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-28x' to each side of the equation. ax + 28x + -28x = 0 + -28x Combine like terms: 28x + -28x = 0 ax + 0 = 0 + -28x ax = 0 + -28x Remove the zero: ax = -28x Divide each side by 'x'. a = -28 Simplifying a = -28
| -10+1=q | | -5t-2(-5t+10)=100 | | -8(-8-6)=-6-22 | | 4x-5=5x-7 | | 12=-6z-6 | | x^3+13=-14 | | -5(9+a)=10 | | 44=t-20 | | 383=8x+7 | | 9=4(5-a) | | 10x+6=6x-3 | | -1(x+8)+9=7x+1-8x | | 2z=19.9 | | -11-5=6(5+4) | | -12=-2p+8 | | 12(3x-7)=-300 | | 2q=3 | | 3q+7=7q | | 0=6x+8 | | (X+0.2)(X+1.5)=0 | | 7q^2-9q-(n+2)=0 | | -4n+9=-7 | | -14+28=-2(x+6) | | 3x=360/4 | | 5(x+12)+7=11 | | 329-9x=14 | | g(20)=210-20(20) | | f(20)=210-20(20) | | (3x+2)(7x-4)=21x^2+10 | | (X-6)+y=12 | | f(20)=330-30(20) | | 15m+0.50=0.25+25m |